Voluntary disclosure with the International Integrated Reporting Council (IIRC) framework and value relevance - Lutfiani, Asri Pangestika; Fatah, Khoirul; Hudaya, Fadli (Journal of Accounting and Investment, 2024)
Research aims: This paper aims to investigate whether voluntary disclosure of integrated reports (IR) with the International Integrated Reporting Council (IIRC) framework influences value relevance in Indonesia.Design/Methodology/Approach: The data covered the period 2017-2022 of all manufacturing companies in Indonesia listed on the Indonesia Stock Exchange (IDX). The total sample of this study was 606 firm-year observations. An IR Score was developed using the International IR Framework 2013, and content analysis was performed to measure IR adoption and practice. This study employed multiple linear regression to test the hypothesis. The authors also used two models: the Pricing Model for testing the main result and the Ohlson Model for testing robustness. Research findings: The result claims that the IR score yielded a positive and statistically significant effect on the value relevance of the company. In other words, companies with higher IR scores will also have a higher value relevance.Theoretical contribution/ Originality: First, this study contributes to the literature in accounting, stating that companies that adopt the IR framework can increase the value relevance. Second, by using different models to test the hypothesis, the results of this paper exhibit a consistent relationship.Practitioner/Policy implication: The study's findings help regulators develop new regulations.Research limitation/Implication: This research could only be generalized to Indonesian manufacturing companies. In addition, a significant number of Indonesian manufacturing companies continue to fail to submit integrated reports.